Quantitative and qualitative analysis of disciplines related to veterinary public health in undergraduate courses in veterinary medicine in Brazil - de Paula, Eric Mateus Nascimento; Bruno Borges Souza, Juliana; Souza Moreira, Thaynara; de Alvarenga Cruz, Carolina; Barbosa Meirelles Bartoli, Raphaella; Brom Vilela, Gabriel; Aparecida Bianco Carvalho, Adolorata (Revista de Ciência Veterinária e Saúde Pública, 2025)
With the emergence of the Unique Health concept, knowledge about zoonoses became substantial elements in the understanding of diseases transmissible to human beings. Thus, the Public Health actions developed by veterinarians have been considered of great value to several international organizations related to health. Thus, the objective of this work is to analyze how the teaching of Veterinary Public Health (VPS) has been in undergraduate courses in Veterinary Medicine in Brazil, thus enabling us to understand whether the professional trained here meets world expectations. A total of 1,292 subjects that are related to SPV were counted. The disciplines of Veterinary Public Health correspond to 513.6 hours, 22.7% of the total disciplines in the Sciences of Veterinary Medicine, being offered between the 6th and 9th periods. The subjects were divided into Preventive Veterinary Medicine and Public Health (MVPSP) and Inspection and Technology of Animal Products (ITPOA). A total of 803 MVPSP subjects were accounted for (average of 303.3 hours) that presented the following content division: infectious and parasitic diseases, including zoonotic diseases (51.1%); epidemiology (16.7%); national and international health policies (15.7%); environmental management (7.0%); health defense and biosafety (6.2%); health planning (3.1%) and production and control of biological and biotechnological products (0.1%). The ITPOA disciplines present an average workload of 210.3 hours for this subarea of ​​the SPV, corresponding to 9.3%. Subjects ranged from 8 to 160 hours of individual workload. It is concluded, therefore, that there is little allocation of workload for the SPV in Brazil and that the distribution of content needs without reformulation to ensure a more balanced training for students. In this way, professionals trained in Brazil will be able to work in all areas of the SPV, strengthening the concept of One Health.